Pentingnya Penyediaan Lingkungan Belajar yang Kondusif Bagi Anak Usia Dini Berbasis Kunjungan Belajar Di Masa New Normal - Sry Anita Rahman (Peneliti.net, 2020)
The implementation of the learning arrangement environment was a process of integrating various components of the environment that could change the influence of behavior children or students so that it is properly facilitated. This implementation was intended to existing environment that was able to stimulate children to optimal learning activities. One of the principles of kindergarten education is the environment must be created in such a way that interesting and fun by paying attention to the safety and comfort that can support learning activities through children's play. At Ash-Shamadi Kindergarten to optimize learning during the new normal era for their students, the teacher conducted a home visit or better known as a study visit to a child's home and it was considered effective during this pandemic, the reason of why just only limited numbers of children allowed gather because the school didn’t officially opened yet. Kindergarten teacher Ash-Shamadi gathers a maximum of 6 children in one visit which is taken from the closest children's house distance to each other. It also emphasizes learning by adjusting the learning environment so the children felt comfortable and doesn’t feel like they have lost their sense of learning at school. Study visits was also considered effective in reducing the spending of quotas for parents, because the schedule has already been determined by the teacher and the children also feel happy because they can gather with their friends even though in a limited number.